تصميم وحدات دراسية إلكترونية باللغة العربية للطلبة الماليزيين بالجامعات الأردنية وفق حاجاتهم في ضوء المدخل الاتصالى الثقافى - ترك، ريم عادل صابر (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2016)
This study aims to design electronic modules in light of communicative and cultural entrances which are linked together and dealt with as one integrated entry. The study shows the modules design criteria from the communicative cultural perspective. The study also aims to set the electronic standards for the design of the units in electronic specifications according to the instructional design template. The study depends on the Dick and Carey (1996) instructional design model. It starts with analyzing needs and characteristics of learners, and ends with a display of design details within the classroom environment.The field study aims to identifies the connectivity needs of Malaysian students who enroll into Jordanian universities; consequently, an electronic module is designed. This study uses the descriptive inductive approach to identify the standards of designing electronic communicative cultural modules. It also adopts the descriptive analytical approach in determining the communicative needs through a questionnaire distributed to Malaysian students in Jordan. The structural approach shares in designing a model of a unit in communicative, electronic and cultural standards. The study reveals the correlation between language, communication and culture. It also proves the efficiency of the use of computers and its multimedia in the development of multi-language skills in all grades and all levels of learners who are studying Arabic as a second language. The findings of the field study identifies the connectivity needs of Malaysian learners attending Jordanian universities where the study shows that there are issential connectivity needs. Finally, this study presents a general vision for a "window to the Arabic Language" programe and a suggested model for an electronic unit with communicative and cultural standards that aim to enable learners to linguistic, communicative and cultural proficiencies